Pengaruh Kinerja Zakat, Gini Rasio dan Angkatan Kerja Terhadap Kemiskinan dengan Indeks Pembangunan Manusia (IPM) Sebagai Variabel Mediasi - Sahara, Duwi Fadilah; Moh. Mukhsin; Elif Pardiansyah (Universitas Muhammadiyah Surabaya, 2025)
The purpose of this study is to analyze and determine the influence of zakat performance, Gini ratio, and labor force on poverty with the Human Development Index as a mediating variable during the period 2019-2024. This study uses a quantitative method with secondary data obtained through literature and documentation studies. The sample in this study consists of 34 provinces in Indonesia selected using purposive sampling. Data analysis was conducted using panel data regression with the assistance of E-Views software. The results of this study indicate that zakat performance, Gini ratio, and labor force have a negative and significant effect on the Human Development Index (HDI), and the Human Development Index (HDI) has a negative and significant effect on poverty. Zakat performance has a negative but insignificant effect on poverty, while the Gini coefficient and labor force have a positive but insignificant effect on poverty. The Human Development Index (HDI) is able to mediate the influence of zakat performance, the Gini coefficient, and the labor force on poverty. Keyword: Zakat performance, Gini ratio, Labor force, Human Development Index (HDI) and poverty